Development of a novel micro-ablation system to realise micrometric and well-defined hydrogel structures for tissue engineering applications. Issue 6 (20th October 2014) - De Maria, C.; Grassi, L.; Vozzi, F.; Ahluwalia, A.; Vozzi, G.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to develop a novel micro-ablation system to realise micrometric and well-defined hydrogel structures. To engineer a tissue it is necessary to evaluate several aspects, such as cell-cell and cell-substrate interactions, its micro-architecture and mechanical stimuli that act on it. For this reason, it is important to fabricate a substrate which presents a microtopology similar to natural tissue and has chemical and mechanical properties able to promote cell functions. In this paper, well-defined hydrogel structures embedding cells were microfabricated using a purposely developed technique, micro-laser ablation, based on a thulium laser. Its working parameters (laser power emission, stepper motor velocity) were optimised to produce shaded "serpentine" pattern on a hydrogel film. Design/methodology/approach – In this study, initially, swelling/contraction tests on agarose and alginate hydrogel in different solutions of main components of cell culture medium were performed and were compared with the MECpH model. This comparison matched with good approximation experimental measurements. Once known how hydrogel changed its topology, microstructures with a well-defined topology were realised using a purposely developed micro-laser ablation system design. S5Y5 neuroblastoma cell lines were embedded in hydrogel matrix and the whole structure was ablated with a laser microfabrication system. The cells did not show damages due to mechanical stress present in the hydrogel matrix and to thermal increase induced by the laser beam. Findings – The hydrogel structure is able to reproduce extracellular matrix. Initially, the hydrogel swelling/contraction in different solutions, containing the main components of the most common cell culture media, was analysed. This analysis is important to evaluate if cell culture environment could alter microtopology of realised structures. Then, the same topology was realised on hydrogel film embedding neuronal cells and the cells did not show damages due to mechanical stress present in the hydrogel matrix and to thermal increase induced by the laser beam. The interesting obtained results could be useful to realise well-defined microfabricated hydrogel structures embedding cells to guide tissue formation Originality/value – The originality of this paper is the design and realisation of a 3D microfabrication system able to microfabricate hydrogel matrix embedding cells without inducing cell damage. The ease of use of this system and its potential modularity render this system a novel potential device for application in tissue engineering and regenerative medicine area.